Strategi Latihan Adaptif dalam Pendidikan Jasmani Inklusif: Efektivitas Pendekatan HIIT dan MICT pada Individu dengan Cerebral Palsy - Intan Savira; M. Furqon Hidayatullah; Slamet Riyadi; Hanik Liskustyawati (Athena: Physical Education and Sports Journal, 2026)
Abstract: Inclusive physical education requires adaptive, evidence-based training strategies to address the commonly reported limitations in aerobic capacity among individuals with Cerebral Palsy. Although High-Intensity Interval Training (HIIT) and Moderate-Intensity Continuous Training (MICT) are increasingly applied in adaptive physical activity and educational settings, their comparative effectiveness and pedagogical implications remain insufficiently synthesized. This study systematically reviewed and critically examined the effects of HIIT and MICT on aerobic capacity in individuals with Cerebral Palsy. A systematic literature review was conducted following PRISMA 2020 guidelines using Scopus, PubMed/MEDLINE, SPORTDiscus, and Google Scholar (2010–2025). From 286 identified records, 12 studies met the inclusion criteria and were included in the qualitative synthesis. Outcomes related to aerobic capacity, cardiorespiratory fitness, and functional endurance were analyzed across educational, clinical, and adaptive physical activity contexts. The findings indicate that both HIIT and MICT consistently improve aerobic capacity, as reflected by VO₂max, VO₂peak, and functional endurance measures. HIIT provides greater time efficiency and higher physiological stimulus, resulting in relatively rapid aerobic adaptations, particularly in individuals with adequate functional capacity. In contrast, MICT produces more stable, safe, and sustainable improvements, supporting its suitability for long-term implementation in inclusive physical education. No evidence demonstrated the absolute superiority of either approach. Overall, the effectiveness of HIIT and MICT is context-dependent and influenced by functional level, exercise tolerance, and pedagogical objectives, supporting an integrative and progressive training strategy for individuals with Cerebral Palsy.